Woods hole mathematics : Perspectives in mathematics and physics - Tongring, Nils; Penner, R. C (Singapore World Scientific Publishing Company, 2004)
This volume presents selected research in the crossroads of contemporary geometry and mathematical physics, including topics such as moduli spaces, operads, arc complexes, contact manifolds, and applications to macromolecular folding and Brownian motion in Hilbert space.
Keywords: Toán học